Comments to Recent Studies Showing Systemic Mechanisms Enabling Drosophila Larvae to Recover From Stress-Induced Damages. (August 2018) - Hayakawa, Yoichi
Compensational recovery from the damage created by stressors is important for all animals. However, how organisms recover from stress-induced negative impacts has been poorly understood. An 1-hour exposure to heat stress at 35°C led to reduced feeding activity of Drosophila melanogaster larvae, which caused reduction in body weight 2 hours after the stress, but not at other times. Such weight losses seem to be rescued by following enhanced feeding activities. We investigated the mechanisms underlying the accelerated feeding activity after the stress-induced reduction in feeding behavior. Our data showed increased expression of sweet taste gustatory receptor genes ( Grs ) and concomitant decreased expression of bitter taste Grs in the mouth parts 2 to 4 hours after the heat treatment for 1 hour. However, nontypical taste Gr expression was not changed. Furthermore, integration of both messenger RNA and protein expression analysis revealed that expression levels of tropomyosin and ATP (adenosine triphosphate) synthase β subunit were significantly increased in their mouths 3 to 5 hours after the heat stress. The increased expression of these genes would contribute to accelerated muscular movement of the mouth hooks. This study indicated that Drosophila larvae possess an efficient systemic mechanism that enables them to recover from growth delay caused by stress conditions.